Endoscopic modalities for upper gastrointestinal leaks, fistulae and perforations. Issue 3 (3rd November 2015) - Talbot, Michael; Yee, Gary; Saxena, Payal
Abstract : Background: Endotherapy techniques are a recent addition to the suite of non‐surgical and minimally invasive strategies to manage patients with perforations, leaks and fistulae. The emergency nature of these conditions and the heterogeneity of pathologies encountered create difficulties when trying to select appropriate tools in these complex situations. The purpose of this article is to review experience at a tertiary academic centre, describe the various endoscopic tools available and the situations where they can be considered for use. Methods: Single‐centre series and review of the published literature. Results: Of 64 patients, 57 were successfully treated using endoscopic therapy, with surgery used only to provide drainage and suture fully covered metal stents in place to prevent migration. Discussion: Selection of an appropriate endotherapy or stent for a patient with an oesophago‐gastric perforation or fistula requires an understanding of the anatomy and physiology underlying the patient's presentation and an understanding of the strengths and weaknesses of the available methods. Standard surgical principles of drainage, avoidance of distal obstruction and nutrition remain central to successful outcomes. A combination of surgical and endoscopic treatments may reduce the number of required treatments and can provide the ability to anchor fully covered stents to prevent them from migrating.